Alveolar Wound Healing After X-Irradiation: A Histologic, Radiographic, and Histometric Study - Guglielmotti, M. B.; Ubios, Angela M.; Cabrini, Rómulo Luis (Elsevier, 1986)
Fil: Guglielmotti, M. B. Comisión Nacional de Energía Atómica; Argentina